Lipid binding attenuates channel closure of the outer membrane protein OmpF - Liko, I; Degiacomi, M; Lee, S; Newport, T; Gault, J; Reading, E; Hopper, J; Housden, N; White, P; Colledge, M; Sula, A; Wallace, B; et al. (National Academy of Sciences, 2018)
Strong interactions between lipids and proteins occur primarily through association of charged headgroups and amino acid side chains, rendering the protonation status of both partners important. Here we use native mass spectrometry to explore lipid binding as a function of charge of the outer membrane porin F (OmpF). We find that binding of anionic phosphatidylglycerol (POPG) or zwitterionic phosphatidylcholine (POPC) to OmpF is sensitive to electrospray polarity while the effects of charge are less pronounced for other proteins in outer or mitochondrial membranes: the ferripyoverdine receptor (FpvA) or the voltage-dependent anion channel (VDAC). Only marginal charge-induced differences were observed for inner membrane proteins: the ammonia channel (AmtB) or the mechanosensitive channel. To understand these different sensitivities, we performed an extensive bioinformatics analysis of membrane protein structures and found that OmpF, and to a lesser extent FpvA and VDAC, have atypically high local densities of basic and acidic residues in their lipid headgroup-binding regions. Coarse-grained molecular dynamics simulations, in mixed lipid bilayers, further implicate changes in charge by demonstrating preferential binding of anionic POPG over zwitterionic POPC to protonated OmpF, an effect not observed to the same extent for AmtB. Moreover, electrophysiology and mass-spectrometry-based ligand-binding experiments, at low pH, show that POPG can maintain OmpF channels in open conformations for extended time periods. Since the outer membrane is composed almost entirely of anionic lipopolysaccharide, with similar headgroup properties to POPG, such anionic lipid binding could prevent closure of OmpF channels, thereby increasing access of antibiotics that use porin-mediated pathways.